Identification of Driving Factors for The Achievement of Rowing Athletes Among Students - Subhana Bella Shafira; Silvy Juditya; Mamat Heryanto (STKIP Pasundan Press, 2025)
This study aims to identify the driving factors behind the achievement of rowing athletes' performance among students. Sports achievement is not only influenced by physical abilities but also by various other supporting factors such as motivation, social environment, facilities and infrastructure, as well as the roles of coaches and parents. This research uses a descriptive qualitative approach with data collection techniques through observation and in-depth interviews. The subjects in this study were student rowing athletesin the Setu Ciburuy area. The results of the study show that the dominant factors driving student athletes’ performance in rowing sports include interrelated internal and external factors. In addition, participation in various competitions is also an important factor in improving athletes’ experience and competitive mentality. These findings are expected toserve as evaluation material for sports clubs, regional authorities, and related institutions in efforts to develop rowing sports achievements among students.